Uninterested adolescents? Reflections of public high school students about their school - Ferreira, Aline Cristina; Gonzales Martins, Letícia; Soares de Jesus, Juliana; Neves, Maura Assad Pimenta; Arinelli, Guilherme Siqueira; Trevisan de Souza, Vera Lucia (Revista de Psicología, 2021)
Anchored in the theoretical-methodological assumptions of historical-cultural psychology, we aim to discuss how freshmen high school students at a state public school apprehend their school and analyse how these perceptions relate to their approach/distance from the teaching-learning processes. We gathered two undergraduate research, one carried out from 86 questionnaires answered by morning class students, and the other from two meetings with 57 evening class students. Results show that these students highlight the school’s material and organizational conditions as aspects that distance them from teaching activities, as well as value the dialogical relationship with the teacher as central to their involvement with knowledge. It is evident that adolescents establish a pragmatic and socializing relationship with school, since attending to it would be a means of getting a job or socializing with colleagues. We conclude that it is necessary to recognize students as active actors in the school’s transformation process and to deconstruct the conception of naturally disinterested adolescents. We emphasize the importance of building spaces for greater student participation in order to encourage new reflections about the school context and its relation with the current and future lives of young people.